1983
DOI: 10.11606/issn.2526-3358.bolzoo.1983.122037
|View full text |Cite
|
Sign up to set email alerts
|

On social regulation in Nannotrigona (Scaptotrigona) postica latreille, with special reference to male production cycles (Hym., Apidae, Meliponinae)

Abstract: São Paulo. 20520 -São Paulo -Bra sil.(recebido em 26.X . 1982)RESUMO -A produção de machos em Nannotrigona (Scaptotrigona) postiça e alguns aspectos correlacionados foram investi gados e os resultados mostram que os fatores extrínsecos co mo temperatura e precipitação, através da sua importância na determinação das floradas e subsequente aumento na disponibi^ lidade de mel e pólen, não são fatores determinantes imedia tos da alta produtividade da colônia e da produção de machos, como consequencia. Os dados tam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1
39

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(99 citation statements)
references
References 1 publication
4
55
1
39
Order By: Relevance
“…S. postica. As in S. depilis, workers in this species were found to lay both trophic and reproductive eggs (Bego 1990). Workers were observed to lay 118 trophic and 73 reproductive eggs.…”
Section: Note Added In Proofmentioning
confidence: 79%
See 3 more Smart Citations
“…S. postica. As in S. depilis, workers in this species were found to lay both trophic and reproductive eggs (Bego 1990). Workers were observed to lay 118 trophic and 73 reproductive eggs.…”
Section: Note Added In Proofmentioning
confidence: 79%
“…Queen policing is well supported in 30 species of ants, bees, and wasps with known colony kin structure (table A1), and it is particularly common in small-colony species, including Halictidae bees (Michener and Brothers 1974), bumblebees (e.g., Free et al 1969;Duchateau 1989), stingless bees (e.g., Sakagami and Oniki 1963;Bego 1990), and small-colony Polistinae and Vespinae wasps (e.g., Saigo and Tsuchida 2004;Wenseleers et al 2005aWenseleers et al , 2005b; table A1). Our analysis also showed that queen policing was significantly more common in species where workers are more related to other workers' sons and in species where worker policing does not occur.…”
Section: Queen Policingmentioning
confidence: 99%
See 2 more Smart Citations
“…Ainda em relação à reprodução, até o momento não foram determinados quais são os fatores que influenciam a produção de sexuados em Meliponini, porém é esperada uma complexa interação entre fatores intrínsecos e extrínsecos à colônia (Bego, 1982). Alguns fatores já foram propostos e sua relação com a produção de sexuados investigada.…”
Section: Introductionunclassified